Healing in Nurses After Assignment in Natural Disasters - Solikhah, Fitriana Kurniasari; Aditya, Ronal Surya (Folia Medica Indonesiana, 2022)
Highlight : • Disasters impact a large number of people, including nurses who are deployed in the disaster relief. • Culturally sensitive psychological first aid sessions, post-assignment in crisis situations monitoring, and grit have implications in pushing the nurses to overcome their trauma and obstacles. • Government policies are also important in helping nurses to heal after deployment in disaster relief. Abstract : Disasters are defined as catastrophic occurrences that impact a large number of people quickly and with an abrupt onset. On average, one natural disaster is reported globally each day. However, the impact of a traumatic occurrence on an individual may be compared to a rock colliding with the surface of a water body. Systematic searches were conducted in Cochrane, Google Scholar, PubMed, Scopus, Embase, and Web of Science databases. The following keywords were used to perform a literature search: